Biomimetic double network hydrogels: Combining dynamic and static crosslinks to enable biofabrication and control cell‐matrix interactions. Issue 22 (4th October 2021) - Aldana, Ana A.; Morgan, Francis L. C.; Houben, Sofie; Pitet, Louis M.; Moroni, Lorenzo; Baker, Matthew B.
Abstract: Hydrogels are promising candidates for recapitulation of the native extracellular matrix (ECM), yet recreating molecular and spatiotemporal complexity within a single network remains a challenge. Double network (DN) hydrogels are a promising step towards recapitulating the multicomponent ECM and have enhanced mechanical properties. Here, we investigate DNs based on dynamic covalent and covalent bonds to mimic the dynamicity of the ECM and enable biofabrication. We also investigate the spatiotemporal molecular attachment of a bioactive adhesive peptide within the networks. Using oxidized alginate (dynamic network, Schiff base) and polyethylene glycol diacrylate (static network, acrylate polymerization) we find an optimized procedure, where the dynamic network is formed first, followed by the static network. This initial dynamically cross‐linked hydrogel imparts self‐healing, injectability, and 3D printability, while the subsequent DN hydrogel improves the stability of the 3D gels and imparts toughness. Rheology and compression testing show that the toughening is due to the combination of energy dissipation (dynamic network) and elasticity (static network). Furthermore, where we place adhesive sites in the network matters; we find distinct differences when an adhesive peptide, Arg‐Gly‐Asp (RGD), is attached to the different networks. This DN strategy bring us closer to understanding and recreating the complex multicomponent ECM—pushing us past a materials view of cell adhesion—while enabling injectabiltiy and printing of tough hydrogels. Abstract :